2016
DOI: 10.15835/nbha44110228
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Molecular Characterization of Major Quince Cultivars from Turkey

Abstract: Quince (Cydonia oblonga Mill.) belongs to the Rosaceae family is native to south-eastern Europa and Asia Minor. It is generally used for table consumption and processed into jam, jelly and marmalade. It is also used as dwarfing rootstock for pear cultivars. In the present study, fruit characteristics and genetic diversity of 17 quince cultivars from Turkey were investigated. For fruit characteristics, 'Bardacik' had the highest fruit weight. The highest SSC/Acidity ratio were obtained from 'Osmancik'. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The fruit weight varied between 334.91 g (Limon) -377.93 g (Gördes) in terms of cultivar averages and 276.34 g -431.34 g in terms of research years average (Table 3). The fruit weight of quince cultivars observed 209.4-272.0 g in quinces from Van district by Tekintas et al (1991); 205.3 g (Limon) -435.0 g (Midilli) in Aegean Region by Ercan et al (1992); 255.56 g-530.0 g in Oltu district by Ercisli et al (1999); 168.9-203.1 g in the Van district by Koyuncu et al (1999);121.84-350.96 g in Gevaş (Van) district by Yarılgac (2001);198.3-452.8 g in Aegean Region by Ercan and Ozkarakas (2005); 257.4-510.4 g in Marmara Region by Buyukyilmaz and Yalcınkaya (2007);269.4-409.6 g in Kalecik clones by Dumanoglu et al (2009);196.93-461.62 g in Çukurova conditions by Kuden et al (2009);194.01-297.86 g in Spain by Rodriguez-Guisado et al (2009); 265.4-415.9 g in some quince clones by Legua et al (2013); 330.08 g (Eşme) -352.86 g (Limon) by Gercekcioglu et al (2014) in Tokat ecology; 349.26 g in Şanlıurfa conditions by Bolat and Ikinci (2015);175.12-329.44 g by Erçisli et al (2015); 88.0-573.0 g by Pinar et al (2016) in quinces in Egirdir conditions; 135.63-530.74 g by Koc and Keles (2018) in Yozgat conditions. Fruit weight seems to be consistent with previous studies.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The fruit weight varied between 334.91 g (Limon) -377.93 g (Gördes) in terms of cultivar averages and 276.34 g -431.34 g in terms of research years average (Table 3). The fruit weight of quince cultivars observed 209.4-272.0 g in quinces from Van district by Tekintas et al (1991); 205.3 g (Limon) -435.0 g (Midilli) in Aegean Region by Ercan et al (1992); 255.56 g-530.0 g in Oltu district by Ercisli et al (1999); 168.9-203.1 g in the Van district by Koyuncu et al (1999);121.84-350.96 g in Gevaş (Van) district by Yarılgac (2001);198.3-452.8 g in Aegean Region by Ercan and Ozkarakas (2005); 257.4-510.4 g in Marmara Region by Buyukyilmaz and Yalcınkaya (2007);269.4-409.6 g in Kalecik clones by Dumanoglu et al (2009);196.93-461.62 g in Çukurova conditions by Kuden et al (2009);194.01-297.86 g in Spain by Rodriguez-Guisado et al (2009); 265.4-415.9 g in some quince clones by Legua et al (2013); 330.08 g (Eşme) -352.86 g (Limon) by Gercekcioglu et al (2014) in Tokat ecology; 349.26 g in Şanlıurfa conditions by Bolat and Ikinci (2015);175.12-329.44 g by Erçisli et al (2015); 88.0-573.0 g by Pinar et al (2016) in quinces in Egirdir conditions; 135.63-530.74 g by Koc and Keles (2018) in Yozgat conditions. Fruit weight seems to be consistent with previous studies.…”
Section: Resultsmentioning
confidence: 96%
“…Ercisli et al (1999) in the quinces of Oltu district reported, fruit width 78. 98-102.37 mm, fruit length 72.58-121.24 mm;Koyuncuoglu et al (1999) in Ekmek quince cultivar observed, fruit width 7.38-7.57 cm, fruit length 8.35 cm; Yarılgac (2001) said that, fruit width was 5.83-8.19 cm, fruit length was 5.64-9.81 cm in Gevas district quinces; Dumanoglu et al (2009) in Kalecik quince clones in Ankara ecological conditions expressed which, fruit width was 77.3-88.3 mm, fruit length was 92.9-112.6 mm; Rodriguez-Guisado et al (2009) recorded that, in quince clones originating from Spain fruit width was 74.53-86.07 mm, fruit length was 76.01-85.62 mm; Gercekcioglu et al (2014) in Eşme and Limon quinces observed that, fruit width was 81.16-90.89 mm, fruit length was 93.63-111.38 mm; according to Bolat and Ikinci (2015) Esme quince cultivar had a fruit width of 87.62 mm, a fruit length of 98.64 mm, and a fruit volume of 429.32 cm 3 ; Pinar et al (2016) examined fruit width of 63.0 mm, fruit length of 50.0 mm; Koc and Keles (2018) said that fruit width was 6.32-9.36 cm, fruit length was 5.32-10.84 cm; Uzun et al (2020) reported that fruit width was between 44.81-79.25 mm and fruit length was between 55.62-94.03 mm in quince genotypes collected from Kayseri district. Emphasizing that the variety has a significant effect on fruit sizes, Ercisli et al (2015) found that fruit width was 68.56-90.53 mm, fruit length was 75.32-91.68 mm, the geometric diameter was 70.72-90.98 mm, and fruit volume was 185.39-391.98 cm 3 in the quince cultivars they examined.…”
Section: Geometric Diameter (Mm)mentioning
confidence: 96%
See 1 more Smart Citation
“…PCA was conducted to obtain a broad view on the correlations between physico-chemical characteristics and determination of the variation sources. Same way was used in lots of Rosaceae members such as cherries [ 18 ], quince [ 19 ] and apricot [ 20 ], including apple [ 21 ]. According to the obtained results, observed variability was explained by seven components.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of variance showed highly significant differences among genotypes for most of measured traits (results are not shown) and then dataset was visualized graphically through GTI biplot which showed that the first two principal components (PC1 and PC2) explained 53% of total variation (31 and 22% for PC1 and PC2, respectively). In study of Pinar et al (2016), fruit characters (Fruit weight, fruit length, fruit width, fruit firmness and pH) were used for the in Turkish quince cultivars to determine genetic variation and their results indicated that observed variation may be used for conservation of genetic resources and programming future breeding studies. In order to distinguish meaningful groups of tester (traits), repeatable patterns among traits have to be demonstrated through GTI biplot analysis and the "which-won-where" view of biplot (Figure 1) showed the outmost genotypes (five landraces in this case) formed a four-side polygon and the biplot was divided into four sectors delimited by the lines perpendicular to each side of the polygon.…”
Section: Resultsmentioning
confidence: 99%